Osteochondral tissue engineering: scaffolds, stem cells and applications - Nooeaid, Patcharakamon; Salih, Vehid; Beier, Justus; Boccaccini, Aldo R. (Journal of Cellular and Molecular Medicine, 2012)
Osteochondral tissue engineering has shown an increasing development to provide suitable strategies for the regeneration of damaged cartilage and underlying subchondral bone tissue. For reasons of the limitation in the capacity of articular cartilage to self-repair, it is essential to develop approaches based on suitable scaffolds made of appropriate engineered biomaterials. The combination of biodegradable polymers and bioactive ceramics in a variety of composite structures is promising in this area, whereby the fabrication methods, associated cells and signalling factors determine the success of the strategies. The objective of this review is to present and discuss approaches being proposed in osteochondral tissue engineering, which are focused on the application of various materials forming bilayered composite scaffolds, including polymers and ceramics, discussing the variety of scaffold designs and fabrication methods being developed. Additionally, cell sources and biological protein incorporation methods are discussed, addressing their interaction with scaffolds and highlighting the potential for creating a new generation of bilayered composite scaffolds that can mimic the native interfacial tissue properties, and are able to adapt to the biological environment. © 2012 The Authors Journal of Cellular and Molecular Medicine © 2012 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.osteoc
Keywords: Bilayered scaffolds; Clinical relevance; Composites; Osteochondral tissue engineering; Scaffold designs; Scaffold fabrication